1991
DOI: 10.1111/j.1432-1033.1991.tb16204.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the existence of distinct transporters for the polyamines putrescine and spermidine in B16 melanoma cells

Abstract: The uptake of intracellular putrescine and spermidine was examined in B16 melanoma cells. It was found that difluoromethylornithine preferentially induced putrescine transport (28-fold) compared to that for spermidine (3.5-fold). Putrescine uptake was partially Na' dependent, whereas spermidine uptake was not. Inhibition studies with the two polyamines showed that putrescine was a poor competitive inhibitor of spermidine uptake, exhibiting a Ki of 69-7.5 pM, whereas the estimated K, for putrescine uptake was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…In contrast, neither putrescence nor cadaverine inhibited transport with high affinity. These data indicate that, unlike some other cultured cell lines [32], the spermine/spermidine transport activity in S2 cells is relatively insensitive to putrescine. We note that this does Table 1 Endogenous polyamine transport activity of Drosophila S2 cells Cell suspensions were assayed for transport activity at both 1 and 5 min.…”
Section: Drosophila S2 Cells Show Spermine and Spermidine Uptakementioning
confidence: 50%
“…In contrast, neither putrescence nor cadaverine inhibited transport with high affinity. These data indicate that, unlike some other cultured cell lines [32], the spermine/spermidine transport activity in S2 cells is relatively insensitive to putrescine. We note that this does Table 1 Endogenous polyamine transport activity of Drosophila S2 cells Cell suspensions were assayed for transport activity at both 1 and 5 min.…”
Section: Drosophila S2 Cells Show Spermine and Spermidine Uptakementioning
confidence: 50%
“…In some mammalian cell lines, such as rat pneumocytes [13,37], polyamine transport has been described to share a highly specific transport system by the different polyamines. However, many different polyamine transport systems have been described in hamster ovary [17] and in Escherichia coli [9]. The present study revealed that putrescine and spermine were able to significantly inhibit the uptake of spermidine in Synechocystis cells by about 40 % and 50 %, respectively ( Table 1).…”
Section: Discussionmentioning
confidence: 48%
“…While the difference in K m between putrescine and spermidine can exist in a single transporter, the differences in normal/induced uptake indicate different characteristics of the carrier transporting each of the polyamines, suggesting different carriers. The existence of at least two transporters has been proposed by other groups as well [19][20][21] There is a debate whether the inward and outward transport of polyamines are mediated by similar or different carriers. Wallace et al suggest the existence of separate transporters for uptake and export of polyamines after showing effects on the former but not on the later using competitive polyamine-uptake inhibitors on human cancer cells [22].…”
Section: Discussionmentioning
confidence: 99%